2020
DOI: 10.4067/s0718-58392020000400515
|View full text |Cite
|
Sign up to set email alerts
|

Black oat (Avena strigosa Schreb.) grazing or silage for small-scale dairy systems in the highlands of central Mexico. Part I. Crop and dairy cow performance

Abstract: Small-scale dairy systems are important worldwide for local and national production, and an option to overcome poverty. Effects of climate change need forage options adapted to future scenarios. This research addressed the hypothesis that black-oat (Avena strigosa Schreb.), either grazing regrowth or as first-cut silage in the dry season, is a forage option for small-scale dairy farmers in the highlands of Mexico. Part I presents performance of crop and dairy cows. There were two experiments. Treatments in Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Fadul-Pacheco et al [ 14 ] previously characterized the SSDS in the study area, and Alfonso-Ávila et al [ 8 ], Martínez-García et al [ 9 ], Celis-Alvarez el al. [ 15 ], López-González et al [ 16 ], Jaimez-García et al [ 17 ], Sainz-Sánchez et al [ 18 ], Plata-Reyes et al [ 19 ], Becerril-Gil et al [ 20 ]; Burbano-Muñoz et al [ 21 ], Carrillo-Hernández et al [ 22 ], Gómez-Miranda et al [ 23 ], González-Alcántara et al [ 24 ], López-González et al [ 25 ], Marín-Santana et al [ 26 ], Rosas-Dávila et al [ 27 ], Vega-García et al [ 28 ], Muciño-Álvarez et al [ 29 ], identified different local feeding strategies used during the rainy and dry seasons. Based on previous research studies, the different feeding scenarios were determined ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fadul-Pacheco et al [ 14 ] previously characterized the SSDS in the study area, and Alfonso-Ávila et al [ 8 ], Martínez-García et al [ 9 ], Celis-Alvarez el al. [ 15 ], López-González et al [ 16 ], Jaimez-García et al [ 17 ], Sainz-Sánchez et al [ 18 ], Plata-Reyes et al [ 19 ], Becerril-Gil et al [ 20 ]; Burbano-Muñoz et al [ 21 ], Carrillo-Hernández et al [ 22 ], Gómez-Miranda et al [ 23 ], González-Alcántara et al [ 24 ], López-González et al [ 25 ], Marín-Santana et al [ 26 ], Rosas-Dávila et al [ 27 ], Vega-García et al [ 28 ], Muciño-Álvarez et al [ 29 ], identified different local feeding strategies used during the rainy and dry seasons. Based on previous research studies, the different feeding scenarios were determined ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Black oat ( Avena strigosa Schreb.) is a cool‐season annual grass with Mediterranean origin and has been used throughout humid subtropical regions for crop and livestock production systems (Restelatto et al., 2014; Ribeiro et al., 2020; Vega‐García et al., 2020). Compared to other cool‐season grasses, black oat is more heat tolerant and disease resistant, which makes it an attractive forage option for humid temperate regions of the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Black oat ( Avena strigosa Schreb.) is a cool‐season annual grass with an origin in the Mediterranean and has been used in crop and livestock systems throughout humid subtropical regions (Restelatto et al., 2014; Ribeiro et al., 2020; Vega‐García et al., 2020). Relative to other cool‐season grasses, black oat is more heat tolerant and disease resistant.…”
Section: Introductionmentioning
confidence: 99%